EVALUATING THE USE OF KITCHEN GARDENING IN RELATION TO THE SOCIO-ECONOMIC CONDITIONS IN LAHORE, PAKISTAN - Muhammad Kashif; Muhammad Atif Nazeer; Muhammad Mohsin; Muhammad Salahuddin; Faiza Sarwar (International Journal of Contemporary Issues in Social Sciences, 2024)
The world population is increasing with acceleration and increasing demands of abode and food. Kitchen gardening is one of the solutions to resolve these issues. Lahore is the second biggest city in Pakistan by population. Kitchen gardening is practicing in the study area. The main purpose of the study is to identify the areas in Lahore city where kitchen gardening is practicing and evaluate how kitchen gardening is good for health and helps to improve the socio-economic conditions. To achieve the objective, a field survey was conducted based on the questionnaire in Data Ganj Buksh Town, Samnabad town and Gulberg in Lahore. The field data was managed in the MS office. While for mapping and data analysis ArcGIS 10.5 has been used. To identify the areas where kitchen gardening is mainly practiced hotspot analysis was performed. Whereas statistical analysis, correlation is done that was shown the strong relationship between the kitchen gardening and kitchen budget. It has been analyzed by the study that vegetables and fruits that grow in kitchen gardens are utilized at the homes. Among them, 76% of respondents were growing only vegetables while 24% were growing both vegetables and fruits. Almost 100% of respondents responded that market’s food products were not fresh. Most kitchen gardeners (81%) were strongly agreed that a kitchen garden has a good impact on health. The kitchen gardeners didn’t use pesticides and fertilizers. As the food quality is another major issue in big cities. Hence, the growing fresh vegetables and fruits at home and reduction in the kitchen budget were the main benefits for kitchen gardening.